Productivity of industrial workers - "Singh, S.K." (Allahabad, 1988)
Productivity of Industrial Workers, is determined by a myriad of factors, both technical and human. All these factors have tendency to act and react upon each other and revolve around the bull eyes each one of them having its own relative importantance and depending upon the natuire of the organisation and the distinctive needs and aspirations of the individual employeees. Our modern managers are so much engorssed with the minutest details of the automation and mechanisations of their industrial systems that they sometimes find it difficult to maintain a judicious balance between their technical and human inputs.
Keywords: Economics